Computational logic in multi-agent systems 12th international workshop, CLIMA XII, Barcelona, Spain, July 17-18, 2011. proceedings - Leite, Joao; Torroni, Paolo; Agotnes, Thomas; Boella, Guido; Torre, Leon van der (Lecture notes in computer science, 2011)
This book constitutes the proceedings of the 12th International Workshop on Computational Logic in Multi-Agent Systems, CLIMA XII, held in Barcelona, Spain, in July 2011. The 22 papers presented were carefully reviewed and selected from 43 submissions. The purpose of the CLIMA workshops is to provide a forum for discussing techniques, based on computational logic, for representing, programming and reasoning about agents and multi-agent systems in a formal way. This volume features five thematic special sessions: secrets and trust, knowledge and beliefs, logics for games and social choice, cooperation, logic and languages, and norms and normative multi-agent systems.